Development and optimisation of an in-service teacher training programme on motivational assessment in physical education. (February 2017) - Slingerland, Menno; Borghouts, Lars; Jans, Liesbeth; Weeldenburg, Gwen; van Dokkum, Gertjan; Vos, Steven; Haerens, Leen
Although assessment practices are commonly part of the physical education (PE) curriculum they may often frustrate rather than support students' basic needs for autonomy, competence and relatedness. Nevertheless, assessment also provides various promising opportunities to support these basic needs and enhance learning in students. In order to address this issue, we developed an in-service teacher training programme that was grounded within contemporary theories on assessment and motivation, and aimed at improving PE teachers' expertise on motivational assessment practices. In close collaboration with PE teachers and other experts in the field an in-service teacher training programme was developed that covered important topics such as quality assessment, motivation and assessment for learning. Specific attention was directed to the translation of theoretical concepts into practical and applicable tools. The in-service training programme was then provided on-site three times to a total of 33 PE teachers (of whom 20 were male (60%) and 12 were female (40%), teaching experience 3–32 years) representing different PE departments. Through an iterative cycle of development, provision, evaluation and adjustment the programme was gradually optimised. Focus group sessions and questionnaires were employed to evaluate various aspects, and identify barriers and success factors. The in-service teacher training programme is a successful first step in improving the expertise of PE teachers to start and develop higher quality and more motivating assessment practices. Nevertheless, in order to generate durable change within daily PE practice, follow-up training sessions or counselling methods (e.g. through communities of practice) are essential to overcome implementation barriers. Development, adjustment and future directions for assessment are discussed.